Evaluation of the Effect of a Topical Gel Form of Pistacia Atlantica and Trachyspermum Ammi on Induced Oral Mucositis in Male Golden Hamsters by Bio-Marker Indices and Stereological Assessment - Nader Tanideh; Abbas Ali Zareh; Mohammad Mehdi Fani; Maryam Mardani; Farnaz Farrokhi; Ali Talati; Omid Koohi Hosseinabadi; Mahsa Kamali (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Oral mucositis (OM) is a common inflammatory complication consequent to chemotherapy or radiotherapy in cancer patients that affects their quality of life. Therefore, finding an effective treatment for OM is always imperative. Purpose: The purpose of this experimental study was to measure the stereological, anti-inflammatory and antioxidant markers of hydro-alcoholic extract of Pistacia Atlantica (P. atlantica) leaves, Trachyspermum Ammi (T. ammi) fruits and their mixture on induced OM in hamsters. Materials and Method: In Experimental study, OM was generated by the method employed by Tanideh et al., in 90 hamsters, by 5-FU (5-fluorouracil 65 mg/kg, IP). All the animals were divided into 5 groups: control, topical gel base, hydro-alcoholic extract 3% of P. atlantica, hydro-alcoholic extract 1% of T. ammi, and a mixture of the extracts of the two plants. On days 13, 15, and 17, the cheek pouch samples were harvested. Stereological scores and the levels of malondialdehyde (MDA), Superoxide dismutase (SOD), myeloperoxidase (MPO), and interleukin-1B (IL-1B) in the pouch tissue were measured. Results: Lower levels of MPO, MDA, and IL-1B and an increase of SOD level were discovered in the mixture-treated group in comparison with other groups. As an aspect of MDA, no significant differences were detected between the topical gel form of P. atlantica and T. ammi groups on days 13 (p= 0.648), 15 (p= 0.981) and 17 (p= 0.540). No variations of MPO were detected among P. atlantica and T. ammi groups on days 13 (p= 0.159) and 15 (p= 0.694); however, the MPO activity of the T. ammi group was significantly lower than the P. atlantica group on day 17 (5.57±0.56 vs. 6.48±0.35 U/ml, p< .001). The volume density of the epithelium increased in the mixture- treated group (p< 0.05). Conclusion: The results of this study indicated that the mixture of P. atlantica leaves and T. Ammi fruits might be effective in the treatment of OM.